Optimisation of Biobriquette Production Enriched with Burning Lighter Materials - Nugraha, Jaenal Ferdiansyah; Wagiman, Wagiman; Wikarta, Jumeri M (Agro Bali : Agricultural Journal, 2025)
. The increasing trend of fossil fuel consumption is inversely proportional to the available natural gas reserves. Renewable energy sources derived from biomass are needed to become alternative fuels, such as biobriquettes. This study aims to optimize biobriquette production by adding burning initiator materials to obtain the best composition that meets the Indonesian National Standard (SNI) and exhibits good ignition characteristics. The experimental design was based on the Taguchi method with an L9 (34) orthogonal array, and the results were statistically analyzed using Grey Relational Analysis (GRA) to evaluate multiple responses. Although the highest Grey Relational Grade (GRG) indicated the theoretical optimum, the confirmation test revealed a slightly different composition with better burning performance. The optimal composition consisted of 3 g of OPEFB (A1), 16 g of PKS (B2), 40% pine sap (C3), and 20% sulfur (D3), producing a moisture content of 1.148%, ash content of 10.75%, volatile matter content of 12.36%, calorific value of 7,223.5 cal‧g-1, initial ignition time of 1.83 s, and burning rate of 0.237 mg‧min-1. These results indicate that the produced biobriquettes meet SNI standards for moisture, volatile matter, calorific value, and have good burning ease.